Features of the course of viral hepatitis A in a child with persistent mixed herpesvirus infection - E. G. Khramtsova; M. D. Subbotina (Лечащий Врач, 2024)
Background. Today in the structure of viral hepatitis viral hepatitis A takes the lead position, the course of typical forms is usually favorable. Over the last few years, however, the frequency of viral hepatitis A has become higher, with increased morbidity in non-endemic areas of the Russian Federation, also with reactivation of chronic herpesvirus infections in re-convalescents of the new coronavirus infection Covid19. The research by the russian scienctists Volynets G. V., Potapov A. S., Pakhomovskaya N. L. in 2011 allowed to diagnose chronic herpesvirus hepatitis in 19.26% of children (18) during the examination of 107 children with chronic diffuse liver diseases. The etiology of liver damage in 39% of cases (7 children) was represented by monoherpesvirus infection: Ebstein – Barr virus infection or human herpes virus type 6. The other cases of chronic herpesvirus hepatitis were due to mixtforms of herpetic pathogens: Ebstein – Barr virus infection and human herpes virus type 6, or herpes simplex virus type 1-2 with human herpes virus type 6. In mixtforms of herpetic hepatitis there was a moderately severe course due to syndromes of cytolysis and cholestasis, but with rapid positive dynamics as a result of anti-herpetic therapy.Objective. To investigate the course of viral hepatitis A in an 8-year-old child with reactivation of herpetic mixt-infection (VEB, CMV, HPV-1, type 2, HHV-6).Materials and methods. The patient had a severe course of viral hepatitis A due to cytolysis syndromes (ALT increased to 76 norms), cholestasis and hepatoprivine syndrome (PTI decreased to 48.6%), associated with activation of persistent herpesvirus infection.Results. There was a rapid positive dynamics of the patient's condition (within 4-5 days) according to laboratory and clinical data on the basis of anti-herpetic therapy (acyclovir) and interferon alfa-2b therapy. In this clinical case during the onset of viral hepatitis A there was reactivation of persistent mixtherpetic infection, and the latter was the trigger for the development of severe form of the underlying disease process.Conclusion. In case of infection with a hepatotropic pathogen (hepatitis A virus) it is recommended to examine for comorbid chronic herpesvirus infection if there are indications, for example, belonging to the group of “frequently ill children”.